Delta endotoxin of Bacillus thuringiensis subsp. israelensis. - Armstrong, J L (1985)
From Bacillus thuringiensis subsp. israelensis, a proteinase-resistant protein was purified which exhibited toxicity to larval mosquitoes and cultured mosquito cells, lysed erythrocytes, and was lethal to mice. To extract the protein, a sporulating culture of B. thuringiensis subsp. israelensis was treated with alkali, neutralized, and incubated with trypsin and proteinase K. It was then purified by gel filtration and DEAE column chromatography. Up to 240 micrograms of toxic protein was purified from 1 g (wet weight) of culture pellet. Two closely related forms of toxic protein were obtained: the 25a and 25b proteins. The two forms comigrated near 25,000 daltons in a sodium dodecyl sulfate-polyacrylamide gel, were serologically related, and showed similar partial protease digestion profiles, but were distinguishable by DEAE chromatography and nondenaturing polyacrylamide gel electrophoresis. Protein sequencing data indicated the 25b protein lacked the two amino acids at the amino terminus of the 25a protein. A Western blot enzyme-linked immunosorbent assay of alkali-solubilized proteins that were not treated with proteases suggested the toxic 25a and 25b proteins were proteolytically derived from a larger molecule of about 28,000 daltons. Alkali-solubilized proteins from an acrystalliferous strain of B. thuringiensis subsp. israelensis and from B. thuringiensis subsp. kurstaki failed to cross-react with antibodies to the 25a protein.